Protection status assessment, prospects and methods of conservation of species of Schivereckia (Draba s. l.; Brassicaceae) in Ukraine - Kagalo, A.; Kolodiy, V.; Lyubinska, L. (Український ботанічний журнал, 2018)
On the basis of generalization of long-term research data on the status of populations and habitats of taxa of Schivereckia Andrz. ex Besser (Draba L. s. l.; Brassicaceae), S. podolica and S. mutabilis (= S. podolica s. l.) in Ukraine, the assessment of their conservation status and state and the recommended optimal modes for their conservation are provided. It has been shown that populations of these taxa are negatively affected by both anthropogenic and natural factors. Anthropogenic factors include pollution by household waste, sewage drains, grazing, trampling, burning, explosive works, mechanical destruction of ecotopes through the extraction of limestone or gravel. Natural factors are cenotic (reduction of competitiveness), biological (declining vitality of populations), physical (water erosion and natural degradation of slopes due to weathering of rocks), and climatic (influence of wind) ones. It is shown that, despite the fact that species of this genus are not directly harvested or destroyed by humans, their populations are indirectly influenced by negative anthropogenic and natural factors listed above. This negatively affects the vitality and viability of its local populations and cenopopulations. In this regard, it is expedient to transfer this species from the category Not Evaluated (currently applied in the Red Data Book of Ukraine) to the category Vulnerable. For further optimization of preservation of this species complex in various localities and habitats, it is advisable to develop appropriate nature conservation management plans, for Podilski Tovtry NNP as an example. Within the framework of such management plans it is advisable to take into account both scientific and administrative actions for species protection, as well as impact of environmental education and possibility of cultivation.